ĐÁNH GIÁ HÀM LƯỢNG KIM LOẠI NẶNG TRONG ĐẤT RỪNG TỰ NHIÊN KHU VỰC TÂY NGUYÊN VÀ MIỀN ĐÔNG NAM BỘ - Đỗ, Thị Tuyết Nhung; Vũ, Thị Minh Châu; Trần, Thị Lệ Thu; Nguyễn, Văn Thịnh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF HEAVY METALS CONCENTRATION IN SOILS IN THE FOREST OF CENTRAL AND SOUTH VIETNAMThe study evaluated the concentrations of some heavy metals (As, Cd, Cr, Cu, Mn, Ni, Pb and Zn) in soils in different forest habitat types in Central and South Vietnam (Yok Don, Bu Gia Map, Bidoup - Nui Ba National Parks). The concentrations of heavy metals are much smaller than the allowable limits according to QCVN 03-MT:2015/BTNMT. The concentrations of heavy metals in soil in Yok Don and Bidoup - Nui Ba National Parks is lower than in Bu Gia Map National Park. The relationship between the accumulation of heavy metals in soil in the study habitats has not been determined. The origin of heavy metals in soils in the study habitats is mainly accumulated from natural processes.